Reinterpreting the Meaning of Qawwam in QS. Al-Nisa [4]:34: An Intertextuality Analysis in The Qur'an with Cross-References - Fauziah, Meilani Nurul; Nidhom, Khoirun; Shofa, Ida Kurnia (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2026)
The interpretation of QS. Al-Nisa [4]:34, particularly the term qawwam, continues to be a subject of debate in exegetical studies because it is often associated with the legitimization of male leadership over women. This study aims to analyze forms of intertextuality in The Qur'an with Cross-References by Mun'im Sirry and to explain the reinterpretation of the meaning of qawwam that emerges through the relationships between verses. This study is a qualitative study based on literature review, employing a descriptive-analytical method and an intertextuality approach. The primary data consists of the book The Qur'an with Cross-References by Mun'im Sirry, while secondary data was obtained from exegetical works, books, and relevant scholarly articles. The results of the study indicate that there are four forms of intertextuality in the book The Qur’an with Cross-References, namely terminological, methodological, receptive, and interpretive intertextuality. The meaning of qawwam is constructed through a system of cross-references by referring to a number of verses, including QS. Al-Baqarah [2]:202, QS.Al-Baqarah [2]:228, QS.Al-Nisa [4]:32, QS.Al-Nisa [4]:128, and QS.Al-Ahzab [33]:35. The relationship between these verses highlights an emphasis on the principle of justice, the balance of rights and obligations, and reciprocity between men and women. In this context, qawwam is not interpreted as the absolute superiority of men over women, but rather as a form of relational and functional responsibility within the domestic sphere. This study demonstrates that the intertextual approach in The Qur'an with Cross-References not only serves as a method for connecting verses but also functions as a hermeneutical strategy in constructing a more contextual and egalitarian reinterpretation of the meaning of qawwam. Penafsiran terhadap QS. Al-Nisa[4]:34, khususnya pada lafaz qawwam, terus menjadi perdebatan dalam studi tafsir karena sering dikaitkan dengan legitimasi kepemimpinan laki-laki atas perempuan. Penelitian ini bertujuan untuk menganalisis bentuk-bentuk intertekstualitas dalam The Qur'an with Cross-References karya Mun'im Sirry serta menjelaskan reinterpretasi makna qawwam yang terbentuk melalui relasi antar ayat. Penelitian ini merupakan penelitian kualitatif berbasis studi kepustakaan dengan menggunakan metode deskriptif-analitis dan pendekatan intertekstualitas. Data primer penelitian berupa buku The Qur'an with Cross-References karya Mun'im Sirry, sedangkan data sekunder diperoleh dari kitab tafsir, buku, dan artikel ilmiah yang relevan. Hasil penelitian menunjukkan bahwa terdapat empat bentuk intertekstualitas dalam buku The Qur’an with Cross-References, yaitu intertekstualitas terminologis, metodologis, reseptif, dan interpretatif. Makna qawwam dibangun melalui sistem cross-references dengan merujuk pada sejumlah ayat, di antaranya QS.Al-Baqarah [2]:202, QS. Al-Baqarah[2]:228, QS.Al-Nisa [4]:32, QS.Al-Nisa [4]:128, dan QS.Al-Ahzab [33]:35. Relasi antar ayat tersebut memperlihatkan adanya penekanan terhadap prinsip keadilan, keseimbangan hak dan kewajiban, serta kesalingan antara laki-laki dan perempuan. Dalam konteks ini, qawwam tidak dimaknai sebagai superioritas mutlak laki-laki atas perempuan, melainkan sebagai bentuk tanggung jawab relasional dan fungsional dalam ranah domestik. Penelitian ini menunjukkan bahwa pendekatan intertekstualitas dalam The Qur'an with Cross-References tidak hanya berfungsi sebagai metode penghubung antar ayat, tetapi juga menjadi strategi hermeneutik dalam membangun reinterpretasi makna qawwam secara lebih kontekstual dan egaliter.